2012
DOI: 10.1002/jmri.23899
|View full text |Cite
|
Sign up to set email alerts
|

Multiphasic contrast‐enhanced MRI: Single‐slice versus volumetric quantification of tumor enhancement for the assessment of renal clear‐cell carcinoma fuhrman grade

Abstract: Purpose To assess the association between clear-cell carcinoma pathology grade at nephrectomy and magnetic resonance imaging (MRI) tumor enhancement. Materials and Methods The Institutional Review Board approved this retrospective study and waived the informed consent requirement. In all, 32 patients underwent multiphase contrast-enhanced MRI prior to nephrectomy. MRI tumor enhancement was measured using two approaches: 1) the most enhancing portion of the tumor on a single slice and 2) volumetric analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Calcification and 60% or more non-enhancing area were commonly present in large tumors, which may explain why these findings were not significant by multivariate analysis in our study. In addition, one previous study showed that decreased tumor vascularity was associated with high grade RCCs (Vargas et al 2013 ). Because the CT protocols of our study group varied somewhat, our ability to evaluate tumor enhancement may have been limited.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Calcification and 60% or more non-enhancing area were commonly present in large tumors, which may explain why these findings were not significant by multivariate analysis in our study. In addition, one previous study showed that decreased tumor vascularity was associated with high grade RCCs (Vargas et al 2013 ). Because the CT protocols of our study group varied somewhat, our ability to evaluate tumor enhancement may have been limited.…”
Section: Discussionmentioning
confidence: 97%
“…There have been few previous reports citing use of magnetic resonance imaging (MRI) to compare Fuhrman grade with imaging characteristics, and the number of cases reported was relatively small (Vargas et al 2013 ; Goyal et al 2012 ; Rosenkrantz et al 2010 ). Computed tomography (CT) is most often used for preoperative evaluation of RCC, and image quality is generally similar across institutions.…”
Section: Introductionmentioning
confidence: 99%
“…We assumed that volumetric assessment may be preferable in light of the great intratumor heterogeneity of RCC [24]. Furthermore, we focused on the clinically important need to single out clear cell RCC—the most aggressive subtype—from all other subtypes, rather than comparing individual pairs of tumor subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The value of quantification of WL tumor enhancement was also explored by Vargas et al 75 for the prediction of RCC grade. In this study, although single-slice ROIs showed no association with grade, lower WL enhancement on nephrographic and excretory phases was associated with higher tumor grade with significant associations observed between tumor grade and mean, median, top 10%, top 25%, and top 50% WL enhancement.…”
Section: Mri Phenotype Of Rccmentioning
confidence: 99%